2021
DOI: 10.1159/000512053
|View full text |Cite
|
Sign up to set email alerts
|

Complete Transurethral Resection before Radical Cystectomy May Improve Oncological Outcomes

Abstract: Objectives: The objective of this study was to assess the impact of complete transurethral resection of bladder tumors (TURBTs) before radical cystectomy on pathological and oncological outcomes of patients with muscle-invasive bladder cancer (MIBC) and high-risk non-MIBC. Materials and Methods: The charts of all patients who underwent radical cystectomy for bladder cancer in 2 academic departments of urology between 1996 and 2016 were retrospectively reviewed. Patients were divided into 2 groups according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…14 Graffeille et al found in a cohort of 486 patients, 18% of whom received NAC, that complete TUR was the strongest factor in multivariable models both associated with pathological outcomes (complete response or downstaging) as well as recurrence-free and cancer-specific survival. 17 Columbia University also recently published their institutional results and found that complete TUR was associated with superior survival outcomes as well as pathological response at cystectomy among patients with clinically localized bladder cancer who received NAC. 16 In combination with this existing literature, our findings suggest that there may be a benefit to maximal TUR prior to NAC and RC in patients with MIBC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Graffeille et al found in a cohort of 486 patients, 18% of whom received NAC, that complete TUR was the strongest factor in multivariable models both associated with pathological outcomes (complete response or downstaging) as well as recurrence-free and cancer-specific survival. 17 Columbia University also recently published their institutional results and found that complete TUR was associated with superior survival outcomes as well as pathological response at cystectomy among patients with clinically localized bladder cancer who received NAC. 16 In combination with this existing literature, our findings suggest that there may be a benefit to maximal TUR prior to NAC and RC in patients with MIBC.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous and glandular differentiations of urothelial carcinoma were included. We excluded patients who were missing information on the completeness of TUR (n[938), had baseline metastatic disease (n [17) , Photocure, Astra-Zeneca, Merck, Fergene, Abbvie, Cleveland Diagnostics, Nucleix, Ambu, Seattle Genetics, Hitachi, Ferring Research, Verity Pharmaceuticals, Virtuoso Surgical, Stimit, Urogen, Vessi, CAPs Medical, Xcures, BMS, Nonagen, Aura Biosciences, Convergent Genomics; E.Y.V. : Consultant: Abbvie, Advanced Accelerator Applications, Bayer, Clovis, Exelixis, Genzyme, Janssen, Merck, Oncternal; W.K.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 , 14 , 18 ] In several retrospective analyses, complete TURBT was associated with a higher rate of down-staging, which was related to better prognosis. [ 14 , 19 , 23 ] For locally advanced tumors, complete TURBT was not theoretically possible, and incomplete TURBT was often correlated with advanced stage disease (T3–T4), which was a predictor of poor prognosis. [ 18 ] Thus, further studies are needed to assess whether advanced stage or incomplete TURBT is a more significant predictor of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 14 ] reported that 34 of 48 patients who underwent complete TURBT had a lower pathologic stage, whereas only 4 of 25 patients achieved down-staging status in the incomplete resection group. Graffeille et al [ 23 ] conducted a multivariate analysis adjusting for multifocality, weight of endoscopic resection specimen, cT4 stage on preoperative imaging, interval between endoscopic resection and RC, neoadjuvant chemotherapy, pT stage, and associated carcinoma in situ, which demonstrated that macroscopically complete endoscopic resection remained the strongest predictor of both pT0 disease (odds ratio, 3.1; p = 0.02) and down-staging (odds ratio, 7.1; p < 0.0001) in RC specimens. Our results were similar to both of these previous studies, which revealed a significant correlation between complete TURBT and down-staging, whereas Zamboni et al [ 18 ] reported that only 8 of 433 patients who underwent complete TURBT had lower pathologic stage, and 6 of 294 patients in the incomplete group had down-staging status ( p = 0.852).…”
Section: Discussionmentioning
confidence: 99%